The banana situation, the "complementary" products and the business dynamics for export of the United Fruit Company in the Costa Rican Caribbean. 1883-1934 - Viales Hurtado, Ronny J. (2001)
The author analyzes the conjuncture of banana production and exports in Caribbean Costa Rica in the period 1883-1934, in order to offer regional data on the functioning of agro- export development and reconsider the concept of the enclave. He studies the circumstances of the banana industry, nominal and real prices of export bananas, and the United Fruit Company’s strategies surrounding alternative export crops in this period.